Resistive Switching Memory of TiO2 Nanowire Networks Grown on Ti Foil by a Single Hydrothermal Method - Xiao, Ming; Musselman, Kevin P.; Duley, Walter W.; Zhou, Norman Y. (Nano-Micro Letters, 2016)
The resistive switching characteristics of TiO2 nanowire networks directly grown on Ti foil by a single-step hydrothermal technique are discussed in this paper. The Ti foil serves as the supply of Ti atoms for growth of the TiO2 nanowires, making the preparation straightforward. It also acts as a bottom electrode for the device. A top Al electrode was fabricated by e-beam evaporation process. The Al/TiO2 nanowire networks/Ti device fabricated in this way displayed a highly repeatable and electroforming-free bipolar resistive behavior with retention for more than 104 s and an OFF/ON ratio of approximately 70. The switching mechanism of this Al/TiO2 nanowire networks/Ti device is suggested to arise from the migration of oxygen vacancies under applied electric field. This provides a facile way to obtain metal oxide nanowire-based ReRAM device in the future. Highlights: 1 TiO2 nanowire networks were grown on Ti foil by a one-step hydrothermal method. 2 Obtained Al/TiO2 nanowire networks/Ti devices showed forming-free resistive switching behavior. Good retention and endurance performance was achieved for the fabricated devices. 3 Switching mechanism is due to migration of oxygen vacancies under electric field.